ANALISIS PENDAPATAN DAN EFISIENSI PEMASARAN IKAN PATIN DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - Ramon Musikal Sazmi; Dwi Haryono; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This study aims to analyze income and marketing efficiency of ‘patin’ fish.  The research location has been chosen purposively in Seputih Raman Subdistrict Lampung Regency.  Data were collected in September-November 2016. This research uses a  survey method.  The census method is used to know farmers’ income on patin fish, and the marketing channel is used by using snowball sampling.  The results showed that patin fish aquaculture is profitable with R/C value of 2.06 and the farmers’ income is Rp61,799,669.90.  There are three channels of patin fish marketing but all of the channels are inefficient. It is seen from the producer share of less than 70 per cent.  Marketing margin and profit margin ratio (PMR) are not prevalent.  Market structure of patin fish in Lampung Tengah district is imperfect competitive market (olygopsoni).Key words:  Catfish, income, marketing efficiency